Ideas, Politics, and The Making of Muslim Democracy: An Historical Trajectory in Indonesia - Munhanif, Ali; Ihsan, A. Bakir (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
Debates regarding the compatibility of Islam and democracy have thrived, with a focus on political moderation and post-Islamism to explain changes among Islamist groups. However, there’s been little exploration into the historical evolution of their ideologies and political preferences in religious politics. This study examines the role of ideas and politics within Muslim organizations, political parties, and the state in Indonesia. It emphasizes the mechanisms behind both ideology and political motivations, showing how political Islam adopted pragmatic behaviour before entering democratic politics. The interaction between the ideological renewals of Muslim thinkers in the 1970s and changes in the state’s institutional arrangement under the New Order drove Islamic transformation. Political institutions shape Islamic political ideas and their manifestation, influencing cultural identity, political mobilization, and negotiation of group claims. Muslim leadership acts as agents in defining religious interests based on institutional markers.